2007
DOI: 10.1021/om700605y
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Umpolung Allylation of Aldehydes by π-Allylpalladium Complexes Containing Bidentate N-Heterocyclic Carbene Ligands

Abstract: A series of π-allylpalladium complexes with neutral monodentate and bidentate ligands were prepared and examined for their ability to undergo stoichiometric umpolung allylation reactions with benzaldehyde. Neutral bidentate N-heterocyclic carbene ligands promote nucleophilic attack. Catalytic allylation reactions of aromatic and aliphatic aldehydes are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…1-Mesitylimidazole, 1-[2,6-(i-Pr) 2 C 6 H 3 ]-imidazole [18], 1-mesityl-3-methyl-imidazolium iodide 5a [19], 1,3-bis(mesityl)-imidazolin-2-ylidene silver chloride 6f [7] and 1,3-bis(2,6-diisopropylphenyl)-imidazol-2-ylidene silver chloride 6g [7] were prepared according to reported procedures. 1 H NMR (400 MHz) and 13 [20], 10 [21], 11 [22], 12 [23,24], 13 [24] and 14 [25] were in accordance with those reported in the literature.…”
Section: General Considerationssupporting
confidence: 89%
See 1 more Smart Citation
“…1-Mesitylimidazole, 1-[2,6-(i-Pr) 2 C 6 H 3 ]-imidazole [18], 1-mesityl-3-methyl-imidazolium iodide 5a [19], 1,3-bis(mesityl)-imidazolin-2-ylidene silver chloride 6f [7] and 1,3-bis(2,6-diisopropylphenyl)-imidazol-2-ylidene silver chloride 6g [7] were prepared according to reported procedures. 1 H NMR (400 MHz) and 13 [20], 10 [21], 11 [22], 12 [23,24], 13 [24] and 14 [25] were in accordance with those reported in the literature.…”
Section: General Considerationssupporting
confidence: 89%
“…1 (d,3H,J = 6.8 Hz),1.17 (d,3H,J = 6.8 Hz). 13 C NMR (100 MHz, CDCl 3 ) d 145. 2, 136.5, 131.8, 130.0, 124.7, 124.6, 121.4, 53.7, 28.7, 24.4, 24.2, 23.4, 23.4 6.93;N,6.88.…”
Section: -(26-diisopropylphenyl)-3-isopropyl Imidazolium Iodide (5e)mentioning
confidence: 99%
“…[21b] As shown in Table 4, complex 7f (5 mol-%) catalyzes the allylation of aromatic aldehydes with cyclohexenyl acetate (19) at room temperature and leads to the formation of the homoallylic alcohols in 40-78 % yields (Table 4, Entries 1-7). High diastereoselectivities were obtained in all cases with syn/anti ratios superior to 98:2.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as presented in the introduction, it was reported that cationic allylpalladium complexes 5, bearing bidentate NHC-P ligands, were able to react directly with stoichiometric amounts of aldehydes in various solvents at 60-70°C to form the corresponding homoallylic alcohols. [19] We tested the reaction of complex 21 with a stoichiometric www.eurjic.orgamount of aldehyde 16a, in the presence of PPh 3 (Scheme 11). However, whatever the conditions used (THF, 20°C or reflux), no formation of 14b was detected after 16 h (Table 5, Entries 1 and 2) and a degradation of the complex was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation